2016
DOI: 10.1007/s00404-016-4181-z
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative local staging of endometrial cancer: the challenge of imaging techniques and serum biomarkers

Abstract: Our results, even the low number of enrolled patients, are promising and may lead to a greater efficiency and lower health care costs in identifying those women who require radical surgery and pelvic lymphadenectomy and should be addressed, in specialized centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 22 publications
2
39
0
2
Order By: Relevance
“…Seventeen studies published between 1994 and 2016 reporting on 1751 patients were included in the final analyses. Among these 1751 women, 288 had cervical invasion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seventeen studies published between 1994 and 2016 reporting on 1751 patients were included in the final analyses. Among these 1751 women, 288 had cervical invasion.…”
Section: Resultsmentioning
confidence: 99%
“…The study design was clearly stated as prospective in 11 studies . The Quality Assessment of Diagnostic Accuracy Studies 2 assessment of the risk of bias and concerns regarding applicability of the selected studies is shown graphically in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis of endometrial neoplasia is made possible with 3D TVUS, even when circumstances do not allow histologic sampling of the endometrium because of cervical stenosis, which may occur. Additionally, it is reasonable to compare the accuracy and cost‐efficiency of the use of US versus MRI for this purpose . Figure shows a US illustration of a case of endometrial carcinoma.…”
Section: Endometrial Carcinomamentioning
confidence: 99%
“…Additionally, it is reasonable to compare the accuracy and costefficiency of the use of US versus MRI for this purpose. [12][13][14] Figure 9 shows a US illustration of a case of endometrial carcinoma.…”
Section: Endometrial Carcinomamentioning
confidence: 99%